The Franciscan martyrs of Japan in the religious culture and art of New Spain and the Viceroyalty of Peru - Kubiak, Ewa; Bieñko de Peralta, Doris (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
The article traces the reception and depiction of the events that took place on 5 February 1597 in Nagasaki, Japan (i.e. the martyrdom of the Franciscans) in the Spanish colonies in America. Accounts describing the death of the friars very quickly reached the territories of New Spain and the Viceroyalty of Peru, and the beatification in 1627 was used as a pretext for preparing publications, organising public celebrations and creating visual representations commemorating the martyrs. The paper characterises multifigure scenes from both Mexico and Peru. It shows representations in several perspectives, presents the iconography and martyrdom tradition of the Franciscan order and characterises various functions of the narrative story glorifying the martyrs in the Far East. The author points out that the visualisations aimed to promote the attitude of a true Christian in the face of danger, which was reflected in American realities during the missionary activities of the friars. The final aspect of the representations, which is characterised in the article, is a didactic and evangelising function of the paintings.